Depletion of nucleophosmin via transglutaminase 2 cross-linking increases drug resistance in cancer cells - Park, Kang-Seo; Han, Byeong-Gu; Lee, Kyoung Hwa; Kim, Dae-Seok; Kim, Jung-Mo; Jeon, Hyesung; Kim, Hyoun Sook; Suh, Se Won; Lee, Eunjoo H.; Kim, Soo-Youl; Lee, Byung Il (ELSEVIER IRELAND LTD, 2009)
It has been suggested that nucleophosmin has an anti-apoptotic function via Bax binding. We found that nucleophosmin is a substrate of transglutaminase 2 (TGase 2) in cancer cells. Increased expression of TGase 2 expression is highly associated with drug resistance, and polymerization of nucleophosmin by TGase 2 also can be correlated with the drug resistance of cancer cells. In the present study, an accumulation of nucleophosmin in cytosol was detected when doxorubicin was treated to cancer cells, and it was found, moreover, that an increase of cytosolic nucleophosmin can result in drug-induced apoptosis. Nucleophosmin was polymerized by TGase 2, and the polymerization was inhibited with the TGase 2 inhibitor, cystamine, in vitro. The nucleophosmin level in the cytosolic cell fraction was reduced when TGase 2 was expressed, and the reduced nucleophosmin level was rescued by cystamine treatment. Moreover, nucleophosmin cross-linked by TGase 2 was eradicated in MCF7 cells via the ubiquitin-proteasomal pathway. in parallel with this nucleophosmin-level restoration, the pro-apoptotic Bax protein level was increased. Therefore, depletion of cytosolic nucleophosmin by TGase 2 can decrease Bax protein stability and lead to anti-apoptosis. Drug-resistant cancer cells became sensitive to doxorubicin treatment when nucleophosmin was expressed in cytosol. Taking these results together, it can be concluded that TGase 2 inhibits accumulation of cytosolic nucleophosmin through polymerization, which results in drug resistance in cancer cells. Crown Copyright (C) 2008 Published by Elsevier Ltd. All rights reserved.
Keywords: NUCLEOLAR PROTEIN B23; TISSUE TRANSGLUTAMINASE; BREAST-CANCER; EXPRESSION; ACTIVATION; APOPTOSIS; CHAPERONE; LINE; IDENTIFICATION; INDUCTION